2012
DOI: 10.1111/j.1751-7893.2012.00344.x
|View full text |Cite
|
Sign up to set email alerts
|

Distress, defiance or adaptation? A review paper of at‐risk mental health states in young offenders

Abstract: The main conclusion is that this population have many risk factors which increase the possibility of developing serious mental health problems, therefore highlighting the need for early intervention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 70 publications
(159 reference statements)
0
12
0
Order By: Relevance
“…Second, provisional psychiatric diagnoses were assessed with the Diagnostic Interview Schedule for Children Version IV (DISC-IV [14];), a structured interview based on the DSM-IV. The three MAYSI-2 subscales for which youth scored above the caution cut-off score were: (1) alcohol and drug misuse (80% of males, 81% of females); (2) anger and irritability (56% of males and 63% of females); (3) depression and anxiety (32% of males and 54% of females). Overall, results using the DISC-IV indicated that 92% of males and 100% of females qualified for at least one diagnosis from the DSM-IV.…”
Section: Mental Health Needs Of Justice-involved Youth Compared To Gementioning
confidence: 99%
See 2 more Smart Citations
“…Second, provisional psychiatric diagnoses were assessed with the Diagnostic Interview Schedule for Children Version IV (DISC-IV [14];), a structured interview based on the DSM-IV. The three MAYSI-2 subscales for which youth scored above the caution cut-off score were: (1) alcohol and drug misuse (80% of males, 81% of females); (2) anger and irritability (56% of males and 63% of females); (3) depression and anxiety (32% of males and 54% of females). Overall, results using the DISC-IV indicated that 92% of males and 100% of females qualified for at least one diagnosis from the DSM-IV.…”
Section: Mental Health Needs Of Justice-involved Youth Compared To Gementioning
confidence: 99%
“…Adolescence is a developmental period characterized by substantial biological, psychological, and social changes. Such changes can lead to risk factors that can increase vulnerability to the development of mental health problems (e.g., changes in mood, conflict with caregivers, identify formation, risky behaviours [1,2];). In fact, recent research has estimated that 10-25% of all youth meet criteria for a mental health disorder [2][3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a recent review, Casswell, French, and Rogers (2012) integrated findings from nine surveys of young offenders' mental health. Although rates of such problems may be higher in institutional settings, it has also been suggested that those remaining in the community may 'self-medicate' to cope with their problems by regular use of alcohol or other drugs .…”
mentioning
confidence: 99%
“…This trend holds true for adolescents as well as adults. The prevalence of mental illnesses is very high among young offenders in the United States and elsewhere (5,6), and the number of juvenile offenders has increased substantially in recent decades (7). Each factor (mental illness and criminal justice involvement) is a well-established risk factor for the other, as well as a host of poor health, social, educational, and economic outcomes (7)(8)(9)(10).…”
mentioning
confidence: 99%